139k views
5 votes
Evaluate.



2
-2
4
undefined

Evaluate. 2 -2 4 undefined-example-1
User Edymerchk
by
6.0k points

1 Answer

4 votes

Answer:

2

Explanation:

We have to get the value of the expression of - ∛(- 8).

Now, we can write the expression as

- ∛(- 8)

=
-\sqrt[3]{-8}

=
-(-8)^{(1)/(3) } {Converting into exponent form}

=
-[(-2)^(3) ]^{(1 )/(3) } {Since (- 2) × (- 2) × (- 2) = - 8}

=
- [(-2)^{3* (1)/(3) } ]{Since we know that
[x^(a)] ^(b) = x^(ab)}

= - [- 2]

= 2 (Answer)

User Alp Altunel
by
6.2k points